Optimalisasi Sumber Daya Manusia dalam Perencanaan Pendidikan Islam - Jamilus, Jamilus; Yenti, Desmy (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the strategies used for the optimization of human resources in Islamic education planning. The method used is literature review. This research is a type of research that collects data from literature. Data collection techniques through references to books, journals, and websites. The initial step of this research is to study the data from previous research related to human resource planning. Data collection through books, journals, and websites. processing data. Data analysis is carried out with stages of data reduction, data presentation, and conclusion drawing. The results showed that the optimization of human resources in Islamic education planning is a crucial step to face the challenges of globalization and technological development. Through proper recruitment, continuous training, performance evaluation, as well as technology implementation, the quality of Islamic education can be improved. Thus, Islamic education can continue to contribute in forming a generation of faith, knowledge, and noble morals. This effort requires cooperation between various parties, including the government, educational institutions, and the community, to realize a superior and competitive Islamic education system